Psychometric evaluation of the Chinese version of fear of hospitalization scale among outpatients: A validation study - Li, Wenbo; Yu, Hongyu; Zhang, Yanli; Li, Bing; Fu, Mingshu (Frontiers in Psychology, 2023)
Background: In China, some patients avoid seeking medical care and are highly sensitive to subsequent medical care because of fear of possible hospitalization after a diagnosis has been established. Early identification of outpatients with high fear of hospitalization is important for clinical staff to develop targeted education and interventions to reduce patients' fear of hospitalization. However, there are currently no tools to assess outpatients' fear of hospitalization in the mainland of China. The purpose of this study was to translate the Fear of Hospitalization (FH) scale into Chinese and to verify its reliability and validity in outpatients. Results: A rigorous translation and revision process resulted in a three-dimensional, 17-item FH scale. It was found that the item-total correlation coefficient in this study ranged from 0.446 to 0.588, and the critical ratio varied from 11.459 to 20.375. Based on the Cronbach’s α value, the Chinese version of the FH scale was 0.849, while the Cronbach’s α value of the dimensions ranged from 0.857-0.902. In terms of split-half reliability and test-retest reliability, the values were 0.910 and 0.868, respectively. The content validity index of the scale was 0.924, which indicates a good level of content validity. According to the eigenvalues, the three-factor structure explained a cumulative 64.788% of the overall variance, and the three-factor structure was supported by data. As a result of the validation factor analysis, all recommended fit indicators were appropriate. Conclusion: Compared with the original version, it has been shown that the Chinese version of the FH scale is valid and reliable among outpatients. The scale can inform the development of educational intervention plans by nursing managers, physicians, and nurses in situations when some patients may feel fearful of possible hospital admission with a high frequency of unpleasantness and embarrassment after a diagnosis has been established. The developed three-factor structured scale will help identify outpatients with a high fear of hospitalization and help clinicians and nurses take actions to reduce this fear of hospitalization among patients and prevent the avoidance of health care use due to fear of hospitalization.